Human Rights Approach in Nepal’s Development Strategies: A Critical Overview - Deo, Sachindra Kumar (NPRC Journal of Multidisciplinary Research, 2026)
Background: The integration of human rights into development policy represents a paradigm shift from econometric growth models to frameworks centered on human dignity, social justice, and institutional accountability. Nepal, undergoing concurrent political democratization, federal restructuring, and constitutional transformation, presents a critical case for examining how the Human Rights-Based Approach (HRBA) has been operationalized within national development strategies. Objective: This paper critically examines the incorporation of HRBA into Nepal’s development agenda, analyzing constitutional and institutional provisions, policy instruments, implementation mechanisms, and the disjuncture between normative commitments and substantive outcomes. It specifically evaluates the role of the National Human Rights Commission, alignment with Sustainable Development Goals, and compliance with international treaty obligations. Methods: The study employs a qualitative research design grounded in descriptive and interpretive analysis of secondary sources. Data were collected through purposive selection of constitutional texts (Constitution of Nepal 2015), national periodic plans (Fifteenth and Sixteenth Plans), legislation, scholarly literature, NHRC reports, and international policy documents. Thematic analysis was conducted using HRBA core principles—participation, accountability, non-discrimination, empowerment, and rule of law—as an analytical framework. Findings: Nepal has achieved substantial normative and institutional progress, including comprehensive justiciable fundamental rights, constitutionalization of the NHRC with Paris Principles accreditation, and systematic integration of HRBA principles into national planning frameworks aligned with SDGs. However, a persistent implementation gap exists, characterized by weak enforcement of NHRC recommendations, limited institutional capacity at provincial and local levels, structural inequalities (caste, gender, ethnicity, geography), low public rights-awareness, and the decoupling of policy discourse from grassroots development practice. A SWOT analysis reveals that while federalism, international partnerships, and social protection expansion offer opportunities, political instability, corruption, and entrenched discrimination remain significant threats. Conclusion: HRBA in Nepal remains more substantiated in constitutional and policy commitments than in transformative development outcomes. Bridging this formal-substantive divide requires strengthening sub-national governance, institutionalizing rights education, ensuring meaningful participation of marginalized groups, reinforcing accountability mechanisms, and allocating resources to rights-centered sectors. Without sustained political will and institutional reform, HRBA risks becoming rhetorical rather than a instrument for reconfiguring state-citizen power relations. Novelty: This study contributes original value by: (1) providing a comprehensive SWOT analysis situating HRBA within Nepal’s post-2015 federal development architecture; (2) critically examining the NHRC’s contested efficacy through an implementation-focused lens rather than formal mandate assessment; (3) synthesizing constitutional, planning, and institutional dimensions to expose the structural determinants of the rights-implementation gap; and (4) locating Nepal’s HRBA experience within broader Global South debates on the translation of international human rights norms into local development practice.